(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Let us now perceive the variables related to the borrowers. Their ’job knowledge’ is the most dominant factor. job knowledge pertains to the proficiency of the borrowers in the methods, processes and procedures of the activities for which funds have been borrowed. It further implies the appreciation of jobs of others, and keeping oneself abreast with the latest developments having relevance to their activities. These aspects of job knowledge are as vital as the technical knowledge of the job. The spectrum of skills required among borrowers is rather quiet wide. Further it would vary for different categories of borrowers depending upon the priority sector to which they belong. The required skills in the case of farmer-borrower would obviously differ from those needed in a promoter of small scale industrial unit or for the same reason, from those which would be considered essential in a retail/professional/ doctor/lawyer/chartered accountant/ mechanic planning to start a repair workshop. Even so, certain common skills of cardinal significance could be mentioned here. It would be better if borrowers of all categories are well versed with the mechanism of planning which provides the desired future state (setting performance standards) and the means of bringing about the future state. Ability to take decisions based on unemotional reasoning and logic, organize and coordinate the resources (gathering and establishing a proper relationship among the needed resources), communicate lucidly, monitor results to manage changes/exigencies for the benefits are some other skills needed in borrowers irrespective of the class to which they hail.